RETHINKING ISLAMIC DIVORCE LAW IN INDONESIA THROUGH JASSER AUDA’S SYSTEMS APPROACH - Fahmi Assulthoni (JURNAL HAKAM, 2026)
The rising rate of divorce in Indonesia reveals a widening gap between normative legal regulations and the evolving social realities of Muslim families. Islamic family law, which aims to preserve marital harmony, is often perceived as overly formalistic and insufficiently responsive to contemporary social and gender dynamics. This study examines Islamic divorce law in Indonesia through the systems theory developed by Jasser Auda within the broader framework of maqasid al-shari‘ah. Using a normative legal approach with qualitative analysis of statutory regulations, the Kompilasi Hukum Islam, Supreme Court regulations, and selected judicial decisions, the study operationalizes the six features of Auda’s systems theory cognitive nature, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness to analyze the structure and implementation of divorce law. The findings reveal several systemic weaknesses, particularly in the effectiveness of mediation, the enforcement of post-divorce financial obligations, and the legal protection of women and children. These issues indicate that divorce regulation operates within a complex interaction between legal norms, judicial practices, and changing social conditions. The study therefore argues that Islamic divorce law in Indonesia should be understood as an open and evolving legal system rather than a purely doctrinal framework. By applying Auda’s systems perspective, this research contributes to extending maqasid analysis beyond normative interpretation toward a systemic evaluation of contemporary Islamic family law.